The Relation between Photoconductivity Threshold and Open-Circuit Voltage in Organic Solar Cells - Grzibovskis, Raitis; Rudušs, Armands; Polaks, Andis (De Gruyter, 2022)
Most of the solar cell parameters (short-circuit current, fill factor, power conversion efficiency) can only be determined by creating and measuring the solar cell. However, there is an empirical relation that links energy level values of the materials in the active layer to an open-circuit voltage (Uoc) of the solar cell. Due to a variety of possible methods used to determine energy level values and the dispersion of obtained results, this estimate is not always correct. Even if correct energy level values are obtained for separate materials, energy level shift takes place at the interfaces when two materials are mixed. That is why a simple and reliable experimental method for Uoc estimation is required. Usually, photoconductivity is used to obtain the energy gap between molecule ionization energy and electron affinity of a single material. When two materials are mixed, direct charge transfer from donor to acceptor molecule can be observed. The threshold energy (ECT) shows the real difference between donor molecule ionization energy and acceptor molecule electron affinity. This difference should correspond to the Uoc. The present study makes the comparison between the open-circuit voltage estimated from material energy level values, the obtained ECT values for various donor:acceptor systems, and the real Uoc obtained from solar cell measurements. Strong correlation between ECT and Uoc is obtained and the photoconductivity measurements can be used in the estimation of Uoc. © 2022 R. Grzibovskis et al., published by Sciendo.--//-- This is an open access article R. Grzibovskis, A. Ruduss, A. Polaks The Relation Between Photoconductivity Threshold and Open-Circuit Voltage in Organic Solar Cells, Latvian Journal of Physics and Technical Sciences 59 (1), 2022; doi:10.2478/lpts-2022-0003; published under the CC BY 4.0 licence.
Financial support provided by Scientific Research Project for Students and Young Researchers No. SJZ/2020/08 implemented at the Institute of Solid State Physics, University of Latvia is greatly acknowledged. Institute of Solid State Physics, University of Latvia as the Centre of Excellence has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART².
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; direct charge transfer; energy levels; open-circuit voltage; organic materials; organic solar cells; photoconductivity